Composite polymer electrolyte, synthetic method and preparation of lithium ion battery
By using composite polymer electrolytes in lithium-ion batteries, combined with specific proportions and synthesis methods, the problems of low ionic conductivity and insufficient mechanical properties of solid electrolytes are solved, and the high rate performance and cycle stability of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411196181.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-25
AI Technical Summary
In existing lithium-ion batteries, the solid electrolyte has low ionic conductivity and insufficient mechanical properties, which affects its practical application.
Compound polymer electrolytes, including polymer matrix, additives, oxide electrolytes and lithium salts, are used to improve the contact between the electrolyte and the electrode material through specific proportions and synthesis methods, and improve conductivity and mechanical properties.
The high ionic conductivity and good mechanical properties of composite polymer electrolytes are achieved, and the rate performance and cycle stability of lithium-ion batteries are improved.
Smart Images

Figure CN119518080A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a composite polymer electrolyte and a synthesis method and preparation of a lithium ion battery. Background Art
[0002] Driven by environmental protection and carbon emission pressure, research on new energy sources is being actively carried out. Among them, lithium-ion batteries have attracted much attention in the field of energy storage and power due to their high specific energy, long cycle life, and low self-discharge. In order to meet the increasingly high requirements for the energy density of lithium-ion batteries, the positive electrode needs to use materials with higher gram capacity, such as lithium-rich manganese-based materials and high nickel materials. Traditional liquid electrolytes have good electrochemical properties, but generally have poor safety problems. Compared with liquid electrolytes, solid electrolytes have good thermal stability and excellent mechanical properties. At the same time, the use of solid electrolytes can reduce the amount of liquid electrolytes used. Among them, polymer solid electrolytes have low cost, good flexibility, easy processing, and certain application prospects, but their ionic conductivity is extremely low, which seriously hinders their practical application. Oxide electrolytes have high conductivity, but the film is brittle, so oxide + polymer composites are often used. However, how to improve the contact between electrolytes and electrode materials and take into account the conductivity and mechanical properties of solid electrolytes is still a technical problem that needs to be solved urgently.
[0003] Therefore, the present application provides a composite polymer electrolyte and a synthesis method and preparation of a lithium ion battery to meet the needs. Summary of the invention
[0004] The purpose of the present application is to provide a composite polymer electrolyte and a synthesis method and preparation of a lithium-ion battery, aiming to solve the problem of improving the contact between the electrolyte and the electrode material and taking into account the conductivity and mechanical properties of the solid electrolyte.
[0005] To achieve the above-mentioned purpose, the present application provides the following technical solution: a composite polymer electrolyte, comprising a polymer matrix, an additive, an oxide electrolyte, a lithium salt and a solvent, wherein the ratio of the oxide electrolyte, the polymer matrix, the additive and the lithium salt is (82-93):(5-10):(1-5):(1.5-3).
[0006] Preferably, the polymer matrix is any one of polyvinylidene fluoride, polyethylene oxide, thermoplastic polyurethane, polypropylene oxide, polycarbonate, polyvinyl alcohol, polyacrylic acid, polyethyl methacrylate, polymethyl methacrylate, polyacrylonitrile or polyvinyl chloride, or a combination of at least two thereof.
[0007] Furthermore,
[0008] Preferably, the additive is disulfide propionitrile, and the added amount is 1%-5wt% of the total dry powder mass of the composite polymer electrolyte.
[0009] Preferably, the oxide electrolyte is LLZO or LLZTO; the oxide electrolyte can be a solid powder or a slurry; the amount of oxide electrolyte dry powder added is 82-93wt% of the total dry powder mass of the composite polymer electrolyte.
[0010] Preferably, the lithium salt is a fluorine-containing lithium salt, and any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate or lithium trifluoromethanesulfonate or a combination of at least two thereof is used; the added amount is 10-30wt% of the total dry powder mass of the composite polymer electrolyte, and too much added amount results in large brittleness of the composite electrolyte film, and too little added amount cannot ensure high ionic conductivity.
[0011] Furthermore, the lithium salt uses lithium bis(trifluoromethylsulfonyl imide) and lithium bis(fluorosulfonyl imide).
[0012] Preferably, the solvent is 1-methyl-2-pyrrolidone.
[0013] A method for synthesizing a composite polymer electrolyte comprises the following steps:
[0014] Step 1, weighing an oxide electrolyte, a polymer matrix, an additive and a lithium salt in proportion, and dispersing them in a 1-methyl-2-pyrrolidone solvent;
[0015] Step 2, add the oxide electrolyte-LLZO, the polymer body-polyvinylidene fluoride, the additive-sulfonyl dipropionitrile, and the 1-methyl-2-pyrrolidone solvent in sequence for high-speed dispersion and vacuum stirring for 2-4 hours;
[0016] Step 3, adding lithium salt-lithium bis(fluorosulfonyl)imide and continuing stirring for 2 hours to obtain a composite polymer solid electrolyte slurry.
[0017] Preferably, in step 1, the weight ratio of the oxide electrolyte, the polymer body, the additive and the lithium salt is 90:5:2:3; and the 1-methyl-2-pyrrolidone solvent accounts for 70% of the total weight.
[0018] A method for preparing a composite polymer electrolyte lithium battery,
[0019] The lithium-ion battery in the technical solution does not include a diaphragm, and includes a positive electrode sheet, a negative electrode sheet, a composite polymer electrolyte and an electrolyte;
[0020] The electrode sheet includes a current collector, an active material layer, and a composite polymer electrolyte layer;
[0021] The active material layer includes an active material, a conductive agent, and a binder;
[0022] Preferably, the active material layer further comprises an oxide electrolyte;
[0023] The binder used in the active material layer and the polymer matrix component used in the composite polymer electrolyte layer may be the same or different.
[0024] Optionally, the mass percentage of the active material to the oxide electrolyte in the active material layer is (80-95):(5-20), adding too much oxide electrolyte will reduce the energy density of the battery, and adding too little oxide electrolyte will not be able to fully disperse inside the electrode to form an ion transmission channel;
[0025] The following steps are involved:
[0026] Step 1, preparing a composite polymer electrolyte slurry, wherein the viscosity of the composite polymer electrolyte slurry is controlled to be 2000-3500 mPa / s;
[0027] Further, the viscosity of the composite polymer electrolyte slurry is preferably controlled to be 2500-3000 mPa / s;
[0028] The oxide electrolyte (LLZO), polymer matrix-polyvinylidene fluoride (PVDF), additive-sulfonyl dipropionitrile (SDPN), lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) are weighed according to the weight ratio and dispersed in 1-methyl-2-pyrrolidone (NMP) as a solvent, and 1-methyl-2-pyrrolidone (NMP) accounts for 70% of the total weight;
[0029] The oxide electrolyte (LLZO), polymer matrix - polyvinylidene fluoride (PVDF), additive - sulfonyl dipropionitrile (SDPN), and 1-methyl-2-pyrrolidone (NMP) were added in sequence for high-speed dispersion and vacuum stirring for 3 hours at a stirring temperature of 45°C, and then lithium salt - lithium bis(fluorosulfonyl)imide (LiFSI) was added and stirring was continued for 2 hours to obtain a composite polymer solid electrolyte slurry.
[0030] Step 2, preparation of positive electrode sheet,
[0031] The positive electrode active material Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , oxide electrolyte (LLZO), conductive agent acetylene black (Super P), binder-polyvinylidene fluoride (PVDF) and carbon nanotubes (CNT) are mixed uniformly according to mass ratio, and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to prepare a uniform black slurry, and the mixed black slurry is coated on both sides of aluminum foil, and then baked and rolled to obtain a positive electrode sheet;
[0032] Step 3, preparation of negative electrode sheet,
[0033] The negative electrode active material graphite, the conductive agent acetylene black (Super P), carboxymethyl cellulose (CMC) and the binder-styrene butadiene rubber (SBR) are mixed uniformly according to the mass ratio, and uniformly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet;
[0034] Step 4, composite polymer electrolyte coating,
[0035] Using a coating device, the dispersed solid electrolyte slurry is evenly coated on the positive electrode sheet, with a thickness of 10-40 μm on the upper and lower surfaces;
[0036] Furthermore, the thickness is 15-25 microns; if the thickness is too thin, the short circuit rate of the battery increases, and if it is too thick, the internal resistance is too large;
[0037] Step 5, electrolyte, injection coefficient is 1.0-2.5Ah / g;
[0038] Further, the preferred micro-electrolyte injection coefficient is 1.5-2.0Ah / g;
[0039] The solvent in the electrolyte used is composed of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, and the lithium salt is 15% by mass of LiPF 6 ;
[0040] Too little electrolyte addition will result in insufficient infiltration of the electrode gaps, affecting the battery's charge and discharge capabilities. Too much electrolyte addition will result in more liquid electrolyte residue inside the battery.
[0041] Step 6, Assembly,
[0042] The positive and negative electrodes prepared in the above steps are stacked in order, and bare cells are obtained through lamination, hot pressing and tab welding. The bare cells are placed in a stamped outer packaging aluminum-plastic film and baked in an oven at 90±10°C for 48 hours. 3 g of the electrolyte prepared in step 5 is injected into the dried battery, and vacuum standing, formation and capacity separation are completed to realize the preparation of the battery.
[0043] In summary, the technical effects and advantages of the present invention are as follows:
[0044] 1. In the present invention, the additive SDPN (sulfonyl dipropionitrile) is added in the synthesis of the composite polymer electrolyte. The nitrile group in the additive structure coordinates with the metal ions in the oxide electrolyte. This strong coordination effect can enhance the bonding strength between the oxide electrolyte and the composite polymer electrolyte. The composite polymer electrolyte is coated around the oxide electrolyte particles, which improves the mechanical strength, toughness and ionic conductivity of the composite polymer electrolyte film. At the same time, the S=O bond in the structure competes with the nitrile group for coordination, reduces the crystallinity of the polymer matrix, and improves the conductivity of the composite polymer electrolyte. The battery prepared based on the composite polymer electrolyte has good rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0046] Figure 1 The battery formation dQ / dV curve of the present invention;
[0047] Figure 2 is the battery formation charging curve of the present invention;
[0048] pass Figure 1 and Figure 2 The formation data analysis shows that after coating with the composite polymer electrolyte, the battery can still be charged normally for the first time, and the dQ / dV curve and the battery can be cycled, which proves that SEI film is formed at the negative electrode interface.
[0049] Figure 3 It is the cycle test data curve of the present invention;
[0050] Figure 4 It is the rate discharge test data curve of the present invention;
[0051] pass Figure 3 and Figure 4 The cycle and rate test data prove that the technical solution provided by the present invention has certain advantages in cycle and rate performance. DETAILED DESCRIPTION
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Embodiment 1:
[0054] A method for preparing a composite polymer electrolyte lithium battery comprises the following steps:
[0055] Step 1, preparing a composite polymer electrolyte slurry,
[0056] The oxide electrolyte (LLZO), the polymer matrix-polyvinylidene fluoride (PVDF), the additive-sulfuryl dipropionitrile (SDPN), and the lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) are weighed according to a weight ratio of 90:5:2:3, and dispersed with 1-methyl-2-pyrrolidone (NMP) as a solvent, and 1-methyl-2-pyrrolidone (NMP) accounts for 70% of the total weight;
[0057] The oxide electrolyte (LLZO), polymer matrix - polyvinylidene fluoride (PVDF), additive - sulfonyl dipropionitrile (SDPN), and 1-methyl-2-pyrrolidone (NMP) were added in sequence for high-speed dispersion and vacuum stirring for 3 hours at a stirring temperature of 45°C, and then lithium salt - lithium bis(fluorosulfonyl)imide (LiFSI) was added and stirring was continued for 2 hours to obtain a composite polymer solid electrolyte slurry.
[0058] Step 2, preparation of positive electrode sheet,
[0059] The positive electrode active material Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , oxide electrolyte (LLZO), conductive agent acetylene black (Super P), binder-polyvinylidene fluoride (PVDF) and carbon nanotubes (CNT) are mixed uniformly in a mass ratio of 91:5:1:1.5:1.5, and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry, and the mixed black slurry is coated on both sides of the aluminum foil, and then baked and rolled to obtain a positive electrode sheet;
[0060] Step 3, preparation of negative electrode sheet,
[0061] The negative electrode active material graphite, the conductive agent acetylene black (Super P), carboxymethyl cellulose (CMC) and the binder-styrene butadiene rubber (SBR) are mixed evenly in a mass ratio of 95:1.5:1.5:2, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet;
[0062] Step 4, composite polymer electrolyte coating,
[0063] Using a coating device, the dispersed solid electrolyte slurry is evenly coated on the positive electrode sheet, with a thickness of 20 μm on the upper and lower surfaces;
[0064] Step 5, electrolyte,
[0065] The solvent in the electrolyte used is composed of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, and the lithium salt is 15% by mass of LiPF 6 ;
[0066] Step 6, Assembly,
[0067] The positive and negative electrodes prepared in the above steps are stacked in order, and bare cells are obtained through lamination, hot pressing and tab welding. The bare cells are placed in an outer packaging aluminum-plastic film that has been punched and formed, and baked in an oven at 90°C for 48 hours. 3 g of the electrolyte prepared in step 5 is injected into the dried battery, and vacuum standing, formation and capacity separation are completed to realize the preparation of the battery.
[0068] Embodiment 2:
[0069] The difference between this embodiment and embodiment 1 is that in the preparation of the composite polymer electrolyte in this embodiment, the additive - sulfonyl dipropionitrile (SDPN) is added in an amount of 1% of the mass of the composite polymer electrolyte dry powder;
[0070] The rest of the preparation methods and parameters were the same as those in Example 1.
[0071] Embodiment 3:
[0072] The difference between this embodiment and embodiment 1 is that in the preparation of the composite polymer electrolyte in this embodiment, the additive - sulfonyl dipropionitrile (SDPN) is added in an amount of 5% of the mass of the composite polymer electrolyte dry powder;
[0073] The rest of the preparation methods and parameters were the same as those in Example 1.
[0074] Embodiment 4:
[0075] The difference between this embodiment and embodiment 1 is that, in the preparation of the composite polymer electrolyte in this embodiment, the amount of lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) added is 10% of the mass of the composite polymer electrolyte dry powder;
[0076] The rest of the preparation methods and parameters were the same as those in Example 1.
[0077] Embodiment 5:
[0078] The difference between this embodiment and embodiment 1 is that, in the preparation of the composite polymer electrolyte in this embodiment, the amount of lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) added is 30% of the mass of the composite polymer electrolyte dry powder;
[0079] The rest of the preparation methods and parameters were the same as those in Example 1.
[0080] Embodiment 6:
[0081] The difference between this embodiment and embodiment 1 is that, in the preparation of the composite polymer electrolyte in this embodiment, the amount of the oxide electrolyte LLZO dry powder added is 82wt% of the total dry powder mass of the composite polymer electrolyte;
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Embodiment 7:
[0084] The difference between this embodiment and embodiment 1 is that, in the preparation of the composite polymer electrolyte in this embodiment, the amount of the oxide electrolyte LLZO dry powder added is 93wt% of the total dry powder mass of the composite polymer electrolyte;
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Embodiment 8:
[0087] The difference between this embodiment and embodiment 1 is that the dispersed solid electrolyte slurry is evenly coated on the positive electrode sheet by using a coating device, with a thickness of 10 μm on the upper and lower surfaces.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Embodiment 9:
[0090] The difference between this embodiment and embodiment 1 is that the dispersed solid electrolyte slurry is evenly coated on the positive electrode sheet by using a coating device, with a thickness of 40 μm on the upper and lower surfaces.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Comparative Example 1:
[0093] The difference between this embodiment and embodiment 1 is that, in the preparation of the composite polymer electrolyte in this embodiment, no sulfonyl dipropionitrile (SDPN) is added.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Comparative Example 2:
[0096] The difference between this embodiment and embodiment 1 is that in the preparation of the composite polymer electrolyte in this embodiment, no oxide electrolyte LLZO dry powder is added.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Comparative Example 3:
[0099] The difference between this embodiment and embodiment 1 is that in the preparation of the composite polymer electrolyte in this embodiment, only the oxide electrolyte LLZO and 1-methyl-2-pyrrolidone (NMP) solvent are used, and only the oxide electrolyte slurry to be coated is synthesized.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Battery performance test:
[0102] Initial battery capacity: At 25±2°C, charge the batteries obtained in each implementation case and comparative example at 1C constant current to 4.2V, then charge at constant voltage to a cutoff current of 0.05C, let stand for 10 minutes, and discharge at 1C constant current to a cutoff voltage of 2.75V, and remember the initial discharge capacity.
[0103] Cycle performance test: At 25±2°C, the soft-pack batteries obtained in each implementation case and comparative example were subjected to charge and discharge cycle tests at a charge and discharge rate of 1C / 1C in the range of 2.75-4.2V, and the battery's first-week discharge capacity and the discharge capacity after 100 cycles were recorded. 100-week capacity retention rate = 100-week discharge capacity / first-week discharge capacity*100%, and the recorded data are shown in Table 1.
[0104] Rate discharge test (3C): At 25±2°C, charge the batteries obtained in each implementation case and comparative example at 1C constant current to 4.2V, then charge at constant voltage to a cutoff current of 0.05C, let stand for 10 minutes, and discharge at 3C constant current to a cutoff voltage of 2.75V. Remember the 3C discharge capacity, and the discharge capacity retention rate = 3C discharge capacity / initial discharge capacity.
[0105] Table 1
[0106] Group Cycle capacity retention rate after 100 cycles (%) 3C discharge capacity retention rate (%) Example 1 88.0% 92.1% Example 2 87.2% 80.5% Example 3 86.2% 81.7% Example 4 86.9% 88.5% Example 5 84.9% 91.2% Example 6 86.4% 88.9% Example 7 84.2% 89.0% Example 8 80.5% 85.0% Example 9 83.6% 79.5% Comparative Example 1 78.2% 80.1% Comparative Example 2 74.5% 52.1% Comparative Example 3 50.4% 68.9%
[0107] Experimental results analysis:
[0108] By comparing the experimental results of Examples 1, 2, 3 and Comparative Example 1, it can be seen that the additive-sulfuryl dipropionitrile (SDPN) can take into account the cycle performance and rate discharge performance of the battery. The amount of additive added is too little, and the effect on ion transmission is not obvious. The nitrile group in the additive structure and the metal ion coordination effect in the oxide electrolyte are weak, and it is impossible to take into account the mechanical strength and toughness and ionic conductivity of the composite polymer solid electrolyte film, and the cycle and rate performance are poor. Too much addition, the nitrile polymerization phenomenon is more obvious, showing that the ionic conductivity is reduced, and the battery rate performance is poor. Therefore, the preferred embodiment 1 of the present invention is the optimal addition amount.
[0109] By comparing the experimental results of Examples 1, 4, and 5, it can be seen that when the amount of lithium salt added is too little, the ionic conductivity of the prepared composite polymer solid electrolyte decreases; when the amount of lithium salt added is too much, the mechanical properties of the composite polymer solid electrolyte membrane are significantly reduced, which is manifested as a decrease in cycle performance.
[0110] By comparing the experimental results of Examples 1, 6, and 7 with Comparative Examples 2 and 3, it can be seen that if the amount of oxide electrolyte LLZO added is too little, the composite polymer electrolyte is mainly based on a polymer matrix, and the battery rate performance is poor. If the amount of oxide electrolyte LLZO added is too much, the brittleness of the composite polymer electrolyte membrane increases, making it difficult to support long-cycle performance tests, and the cycle performance decreases.
[0111] By comparing the experimental results of Examples 1, 8, and 9, it can be seen that if the coating thickness is too thin, the measured battery short-circuit rate increases, resulting in large battery self-discharge, which is manifested as a decrease in battery cycle performance. If the coating thickness is too thick, the battery internal resistance increases, the electrolyte infiltration effect is poor, and the battery cycle performance and rate performance deteriorate.
[0112] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite polymer electrolyte, characterized in that: It includes a polymer matrix, an additive, an oxide electrolyte, a lithium salt and a solvent, and the ratio of the oxide electrolyte, the polymer matrix, the additive and the lithium salt is (82-93):(5-10):(1-5):(1.5-3).
2. A composite polymer electrolyte according to claim 1, characterized in that: The polymer matrix is any one of polyvinylidene fluoride, polyethylene oxide, thermoplastic polyurethane, polypropylene oxide, polycarbonate, polyvinyl alcohol, polyacrylic acid, polyethyl methacrylate, polymethyl methacrylate, polyacrylonitrile or polyvinyl chloride, or a combination of at least two thereof.
3. A composite polymer electrolyte according to claim 1, characterized in that: The additive is disulfide propionitrile, and the added amount is 1%-5wt% of the total dry powder mass of the composite polymer electrolyte.
4. A composite polymer electrolyte according to claim 1, characterized in that: The oxide electrolyte is LLZO or LLZTO.
5. A composite polymer electrolyte according to claim 1, characterized in that: The lithium salt is a fluorine-containing lithium salt, and is any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate or lithium trifluoromethanesulfonate, or a combination of at least two thereof; the added amount is 10-30wt% of the total dry powder mass of the composite polymer electrolyte.
6. A composite polymer electrolyte according to claim 1, characterized in that: The solvent is 1-methyl-2-pyrrolidone.
7. A method for synthesizing a composite polymer electrolyte, characterized in that: The following steps are involved: Step 1, weighing an oxide electrolyte, a polymer matrix, an additive and a lithium salt in proportion, and dispersing them in a 1-methyl-2-pyrrolidone solvent; Step 2, add the oxide electrolyte-LLZO, the polymer body-polyvinylidene fluoride, the additive-sulfonyl dipropionitrile, and the 1-methyl-2-pyrrolidone solvent in sequence for high-speed dispersion and vacuum stirring for 2-4 hours; Step 3, adding lithium salt-lithium bis(fluorosulfonyl)imide and continuing stirring for 2 hours to obtain a composite polymer solid electrolyte slurry.
8. The method for synthesizing a composite polymer electrolyte according to claim 7, characterized in that: In step 1, the weight ratio of the oxide electrolyte, the polymer body, the additive and the lithium salt is 90:5:2:3; the 1-methyl-2-pyrrolidone solvent accounts for 70% of the total weight.
9. A method for preparing a composite polymer electrolyte lithium battery, characterized in that: The following steps are involved: Step 1, preparing a composite polymer electrolyte slurry, The oxide electrolyte (LLZO), polymer matrix-polyvinylidene fluoride (PVDF), additive-sulfonyl dipropionitrile (SDPN), lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) are weighed according to the weight ratio and dispersed in 1-methyl-2-pyrrolidone (NMP) as a solvent, and 1-methyl-2-pyrrolidone (NMP) accounts for 70% of the total weight; The oxide electrolyte (LLZO), polymer matrix-polyvinylidene fluoride (PVDF), additive-sulfonyl dipropionitrile (SDPN), 1-methyl-2-pyrrolidone (NMP) were added in sequence for high-speed dispersion and vacuum stirring for 3 hours at a stirring temperature of 45°C, and then lithium salt-lithium bis(fluorosulfonyl)imide (LiFSI) was added and stirred for 2 hours to obtain a composite polymer solid electrolyte slurry; Step 2, preparation of positive electrode sheet, The positive electrode active material Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, oxide electrolyte (LLZO), conductive agent acetylene black (Super P), binder-polyvinylidene fluoride (PVDF) and carbon nanotubes (CNT) are mixed uniformly according to mass ratio, and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry, and the mixed black slurry is coated on both sides of aluminum foil, and then baked and rolled to obtain a positive electrode sheet; Step 3, preparation of negative electrode sheet, The negative electrode active material graphite, the conductive agent acetylene black (Super P), carboxymethyl cellulose (CMC) and the binder-styrene butadiene rubber (SBR) are mixed uniformly according to the mass ratio, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked, rolled and cut into pieces to obtain the negative electrode sheet; Step 4, composite polymer electrolyte coating, Using a coating device, the dispersed solid electrolyte slurry is evenly coated on the positive electrode sheet, with a thickness of 10-40 μm on the upper and lower surfaces; Step 5, electrolyte, The solvent in the electrolyte used is composed of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7, and the lithium salt is 15% by mass of LiPF6; Step 6, Assembly, The positive and negative electrodes prepared in the above steps are stacked in order, and bare cells are obtained through lamination, hot pressing and tab welding. The bare cells are placed in a stamped outer packaging aluminum-plastic film and baked in an oven at 90±10°C for 48 hours. 3 g of the electrolyte prepared in step 5 is injected into the dried battery, and vacuum standing, formation and capacity separation are completed to realize the preparation of the battery.